2019
DOI: 10.29244/jcs.4.1.37-47
|View full text |Cite
|
Sign up to set email alerts
|

Customer Purchase Intention on Sharia Mutual Fund Products: A TPB Approach

Abstract: This study aimed to determine the influence of variables in TPB (attitude toward behavior, perceived behavioral control, subjective norm), religiosity, knowledge, and risk perception to intention purchase of sharia mutual fund. The sample in this study was customer of Bank Sharia XYZ of 164 customers. The analysis applied in this study was Structural Equation Modeling-Partial Least Square. The result of this research showed that the independent variable had positive and significant influence to dependent varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 9 publications
4
22
1
1
Order By: Relevance
“…Other research conducted by Ali, Zani and Kasim (2014), showed that attitude and perceived behavioural control had a significant and positive influence on investor intentions to invest in Islamic unit trusts. Research conducted by Octarina, Hartoyo and Beik (2019) found that although attitude and subjective norm had a positive and significant effect, the perceived behavioural control variable did not influence the intention to invest in Sharia mutual fund products.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…Other research conducted by Ali, Zani and Kasim (2014), showed that attitude and perceived behavioural control had a significant and positive influence on investor intentions to invest in Islamic unit trusts. Research conducted by Octarina, Hartoyo and Beik (2019) found that although attitude and subjective norm had a positive and significant effect, the perceived behavioural control variable did not influence the intention to invest in Sharia mutual fund products.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Based on previous research, the rejection of the hypothesis of the influence between perceived behavioural control on intention also appears in the results of Octarina, Hartoyo and Beik (2019) which showed that attitude and subjective norm had a positive and significant effect. Still, the perceived behavioural control variable did not affect the intention to invest in Sharia mutual funds products in Indonesia.…”
Section: The Effect Of Perceived Behavioural Control On the Intentions Of Employees To Invest In Retail Bond Productsmentioning
confidence: 94%
“…As for risk knowledge, we were unable to find any research that explicitly examined this. However, we assume that risk knowledge is part of financial knowledge, so we connected previous research that links financial knowledge and investment decision behaviour, such as the studies by Njuguna, Namusonge, and Kanali (2016), Raut (2020), Octarina, Hartoyo, and Beik (2019) and Popat and Pandya (2018). Raut (2020) found a significant effect between financial knowledge and investment decision-making.…”
Section: Previous Studymentioning
confidence: 98%
“…His research makes a significant contribution to financial studies regarding the individual investor's decision-making. Octarina et al (2019) analysed the investment intention of sharia mutual fund products in Indonesia and found that knowledge had a significant influence. Njuguna et al (2016), meanwhile, found that people with financial knowledge who understood the difference between mutual funds and stocks were willing to take risks as part of the investment decision-making process.…”
Section: Previous Studymentioning
confidence: 99%
“…Hasil pengujian menunjukkan bahwa norma subjektif tidak mempengaruhi minat investasi. Hasil ini tidak sejalan dengan penelitian Akhtar dan Das (2019); Octarina et al (2019); Mahardhika and Zakiyah (2020), namun sesuai dengan penelitian Warsame dan Ireri (2016) dan Salisa (2021). Dukungan dari teman, keluarga, dan orangorang terdekat tidak mampu mempengaruhi minat seseorang untuk berinvestasi.…”
Section: Norma Subjektif Terhadap Minat Investasiunclassified